British universities in the Brexit moment : political, economic and cultural implications - Finn, Mike (Great debates in higher education, 2018)
This timely provides an invaluable analysis of the impact the Brexit decision has, and will have, on Britain's universities. International by nature, British universities draw their students and staff from across the global community. Britain is a major beneficiary of EU-sponsored research funding through the Horizon 2020 scheme and partnerships as part of the European Research Area. Britain's universities have world-leading reputations, with the UK sector second only to the United States in international prestige. Brexit has - already - affected this, with a drop in student recruitment from abroad and an increase in EU academics electing to leave the British university system. British Universities in the Brexit Moment offers the first book-length treatment of these issues. It situates the 'Brexit question' in the context of prevailing developments in UK higher education such as marketization and provides an indispensable guide to the material impacts of Brexit on Britain's universities.